2003
DOI: 10.1075/aicr.48.09ash
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive neuroscience of implicit category learning

Abstract: There is much recent interest in the question of whether people have available a single category learning system or a number of qualitatively different systems. Most proponents of multiple systems have hypothesized an explicit, rule-based system and some type of implicit system. Although there has been general agreement about the nature of the explicit system, there has been disagreement about the exact nature of the implicit system. This chapter explores the question of whether there is implicit category lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 113 publications
3
27
0
Order By: Relevance
“…The sensitivity of areas of caudate that were important for classification (e.g., the body and tail of the caudate) to feedback is consistent with theories that the striatum may play a general role in reward-mediated learning (Ashby and Casale, 2003). Behavioral and neuropsychological studies show that categorization learning is dependent on the presence of feedback.…”
Section: Role Of Caudate In Feedback-related Learningsupporting
confidence: 81%
See 3 more Smart Citations
“…The sensitivity of areas of caudate that were important for classification (e.g., the body and tail of the caudate) to feedback is consistent with theories that the striatum may play a general role in reward-mediated learning (Ashby and Casale, 2003). Behavioral and neuropsychological studies show that categorization learning is dependent on the presence of feedback.…”
Section: Role Of Caudate In Feedback-related Learningsupporting
confidence: 81%
“…The involvement of the body and tail of the caudate in learning is consistent with a large body of research with monkeys (Brown et al, 1995;Levy et al, 1997;Teng et al, 2000;Fernandez-Ruiz et al, 2001). Performance on complex visual stimulus-outcome tasks is impaired in patients with compromised striatal functioning (Knowlton et al, 1996a,b;Filoteo et al, 2001 (1998) and Ashby and Casale (2003) that the "visual" corticostriatal loop underlies human classification learning via feedback. ROI analyses indicated that the putamen was significantly activated during classification learning, with a pattern of activity more similar to the pattern in the body and tail of the caudate than the head of the caudate.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…A important debate in the modern perceptual classification literature concerns the issue of whether or not multiple cognitive systems underlie the learning and representation of perceptual categories (Ashby & Casale, 2003;Knowlton & Squire, 1993;Nosofsky & Johansen, 2000;Palmeri & Flanery, 2002;Shanks & St. John, 1994;Smith, Patalano, & Jonides, 1998). Much of the evidence for distinct representational systems is based on the demonstration of a variety of experimental dissociations involving classification performance.…”
Section: Dissociations and Multiple-categorization Systemsmentioning
confidence: 99%